The Vamana avatar of Vishnu - Temples of India Project Team (Jio Institute, 2024)
Vamana is depicted as a dwarf with a potbelly in the Vamana Temple. He had four arms which are all broken presently. He is heavily bejewelled and wears a long vanamala (forest flowers garland). He is accompanied by six attendants who can be seen at the bottom. There are two more figures on his sides, near his arms. Notably, miniature niches at the top of the sculpture house representations of the Hindu trinity; Brahma, Vishnu, and Mahesha.